High-CTI (comparative tracking index) polycarbonate composite material and preparation method thereof

By introducing siloxane PC resin and flame-retardant segments into polycarbonate materials, an inorganic oxygen-barrier heat insulation protective layer is formed, solving the balance problem between flame-retardant performance and mechanical properties of polycarbonate materials. This achieves high CTI value and excellent mechanical properties, making it suitable for high-power and high-voltage scenarios.

CN121673799APending Publication Date: 2026-03-17GUANGDONG GREAT MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610101881.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-26
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing polycarbonate materials struggle to balance flame retardancy and mechanical properties, especially in high-power, high-voltage applications where the addition of traditional flame retardants and anti-dripping agents negatively impacts the overall performance of the material.

Method used

A polycarbonate composite material was prepared by mixing PC resin, siloxane PC resin and polybutylene terephthalate, adding reinforcing fillers and additives. The CTI value was improved by introducing flame-retardant segments and Si-O bonds to form an inorganic oxygen-barrier heat insulation protective layer, and the molecular chain rigidity was enhanced by phenyl groups.

Benefits of technology

It achieves a high CTI value and excellent flame retardant properties while maintaining good mechanical properties, preventing polycarbonate from dripping during combustion and reducing the arc propagation path, making it suitable for high-power, high-voltage scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_10
    Figure SMS_10
Patent Text Reader

Abstract

The invention relates to the field of polycarbonate materials, in particular to a high-CTI polycarbonate composite material and a preparation method thereof.The polycarbonate composite material is prepared from, by weight, 35%-45% of PC resin, 10%-18% of siloxane PC resin, 10%-12% of polybutylene terephthalate, 0.2%-0.6% of an antioxidant, 0.5%-1% of an ultraviolet absorbent, 0.4%-1% of a flame retardant, 1%-5% of toner and the balance reinforcing filler. The polycarbonate composite material disclosed by the invention is excellent in mechanical property and flame retardant property, has a high CTI (Comparative Tracking Index) value, and has an excellent application prospect in a high-power and high-voltage scene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polycarbonate materials, and more specifically to a high CTI polycarbonate composite material and its preparation method. Background Technology

[0002] Polycarbonate (PC) materials are widely used in new energy components and equipment due to their excellent mechanical properties, dimensional stability, and thermal properties, such as electric vehicle charging gun heads / bodies, wiring harness connectors, photovoltaic connectors, and energy storage connectors. However, electronic devices are highly susceptible to localized overheating and even combustion when subjected to overload, short circuit, or leakage. Therefore, the electronics manufacturing industry has stringent requirements for the flame-retardant properties of materials. Traditionally, flame-retardant requirements are met by directly adding flame retardants, but this weakens the material's mechanical and electrical insulation properties. Furthermore, additional additives such as anti-dripping agents are needed to address dripping issues during polycarbonate combustion, which undoubtedly increases the difficulty and cost of applying polycarbonate materials.

[0003] Invention patent CN110028772A discloses a halogen-free flame-retardant glass fiber mineral-reinforced high-CTI polycarbonate, specifically relating to the field of engineering plastics, including main materials and auxiliary materials. The main materials are characterized by a reinforcing carrier, a light-transmitting carrier, and polycarbonate, while the auxiliary materials include a flame-retardant carrier, toughening agent, antistatic agent, UV absorber, lubricant, anti-dripping agent, and antioxidant. Invention patent CN112341779A discloses a high-CTI halogen-free flame-retardant reinforced polycarbonate, its preparation method, and its application. The high-CTI halogen-free flame-retardant reinforced polycarbonate in this invention comprises the following components by mass percentage: polycarbonate 60... 70% silane coupling agent modified glass fiber 20 30%, phosphorus-based flame retardant 5 8%, nitrogen-based flame retardant 2 8%, toughening agent 2 8% stabilizer 0.4% 0.6% antioxidant, 0.01% antioxidant 0.5% lubricant 0.5% 1% and light shielding agent 0.01 1.0%; The high CTI halogen-free flame-retardant reinforced polycarbonate described in this invention achieves halogen-free flame retardancy in the composite material, while also possessing excellent mechanical properties and a high CTI value, making it more suitable for the preparation of engineering plastics in the electronics and electrical appliance fields. However, the aforementioned inventions all involve directly adding large amounts of flame retardants and anti-dripping agents to the system to maintain flame retardant performance, which may affect the mechanical properties of the material, such as tensile properties, causing the overall performance of polycarbonate to be insufficient in more application scenarios and under more specific requirements. Summary of the Invention

[0004] To address the problems existing in the prior art, the present invention aims to provide a polycarbonate composite material with high CTI. The polycarbonate composite material of the present invention exhibits excellent mechanical and flame-retardant properties, and possesses a high CTI value, making it highly promising for applications in high-power, high-voltage scenarios.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a high CTI polycarbonate composite material, which, by weight 100%, comprises the following raw materials: 35-45% PC resin, 10-18% siloxane PC resin, 10-12% polybutylene terephthalate, 0.2-0.6% antioxidant, 0.5-1% ultraviolet absorber, 0.4-1% flame retardant, 1-5% colorant, and the balance being reinforcing filler.

[0006] The present invention preferably uses a mixture of PC resin, siloxane PC resin and polybutylene terephthalate, adding reinforcing fillers as functional fillers, and then preparing a polycarbonate composite material with antioxidants, ultraviolet absorbers, flame retardants and colorants. This composite material has excellent mechanical properties and flame retardant properties, and has a high CTI value, showing excellent application prospects in high-power and high-voltage scenarios.

[0007] In some embodiments of the present invention, the PC resin is PC 2805.

[0008] In some embodiments of the present invention, the preparation steps of the siloxane PC resin are as follows: (1) Under an inert atmosphere, 4-allyl-2-methoxyphenol and 1,1,3,3-tetramethyldisiloxane were mixed and added to toluene, and then a catalyst was added. The mixture was heated to 70-75°C in a water bath and reacted for 8-9 hours. The intermediate was obtained by rotary evaporation. (2) In the reactor, the intermediate and bisphenol A are mixed, alkali solution and dichloromethane are added and stirred, and the mixture is heated to 40~45℃ in a water bath. Catalyst is added, then triphosgene is added dropwise, potassium 2,5-dihydroxybenzenesulfonate is added, and catalyst is added again. The reaction is carried out for 60~80 minutes. After separation, washing and rotary evaporation, a solid is obtained. After washing and drying, siloxane PC resin is obtained.

[0009] In some embodiments of the present invention, the mass ratio of 4-allyl-2-methoxyphenol and 1,1,3,3-tetramethyldisiloxane in step (1) is (2.45~2.8):1.

[0010] In some embodiments of the present invention, the mass ratio of the intermediate to bisphenol A in step (2) is (0.08~0.13):1.

[0011] In some embodiments of the present invention, the mass ratio of potassium 2,5-dihydroxybenzenesulfonate and bisphenol A in step (2) is (0.05~0.1):1.

[0012] The siloxane PC resin added in this invention combines the high mechanical strength of polycarbonate with the flexibility of Si-O bonds on siloxane, exhibiting good impact resistance and tensile strength; at the same time, the branched structure introduced during the preparation of the siloxane PC resin reduces the tendency of electrical tracking and improves the CTI value. This invention also introduces flame-retardant segments into the polycarbonate structure. Compared to directly adding multiple flame retardants, the presence of siloxane, phenyl, and sulfonic acid groups makes the siloxane PC resin containing these flame-retardant segments more compatible with the system. It can achieve excellent synergistic flame-retardant effects with a small amount of addition. At the same time, when the composite material is burning, the siloxane may migrate from the interior of the PC to the surface and accumulate to form a homogeneous inorganic oxygen-barrier and heat-insulating protective layer containing Si-O and Si-C bonds. It also crosslinks with the polycarbonate to form a network structure, which captures and fixes the molten drips, avoids the problem of polycarbonate burning and dripping, reduces the propagation path of the electric arc, and synergistically improves the CTI value. The simultaneous introduction of phenyl increases the rigidity and regularity of the molecular chain, making up for the adverse effects of the flame-retardant molecular chain on the mechanical properties of the system.

[0013] In some embodiments of the present invention, the intrinsic viscosity of the polybutylene terephthalate is 0.8-1.2 dL / g.

[0014] In some embodiments of the present invention, the reinforcing filler is one or any combination of glass fiber, calcium carbonate whiskers and silicon carbide whiskers.

[0015] In some embodiments of the present invention, the antioxidant is one or any combination of antioxidant 168, antioxidant 1010 and antioxidant 1076.

[0016] In some embodiments of the present invention, the flame retardant is a phosphorus-based flame retardant and / or a nitrogen-based flame retardant.

[0017] In some embodiments of the present invention, the ultraviolet absorber is UV-531 and / or UV-326.

[0018] A second aspect of the present invention also provides a method for preparing a high CTI polycarbonate composite material, comprising the following steps: The dried PC resin, siloxane PC resin, polybutylene terephthalate, reinforcing filler, antioxidant, ultraviolet absorber, flame retardant and colorant are stirred in a high-speed mixer to obtain a mixture, which is then transferred to a twin-screw extruder and melt-extruded and granulated to obtain a high CTI polycarbonate composite material.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) In this invention, a polycarbonate composite material is prepared by mixing PC resin, siloxane PC resin and polybutylene terephthalate, adding functional fillers and additives. The composite material has excellent mechanical properties and flame retardant properties, and has a high CTI value, which has excellent application prospects in high power and high voltage scenarios.

[0020] (2) The siloxane PC resin added in this invention combines the high mechanical strength of polycarbonate with the flexibility of Si-O bonds on siloxane, and has good impact resistance and tensile strength; at the same time, the branched structure introduced during the preparation of siloxane PC resin reduces the tendency of electrical tracking and improves the CTI value.

[0021] (3) The present invention also introduces flame-retardant segments into the polycarbonate structure. Compared with the direct addition of multiple flame retardants, the presence of siloxane, phenyl and sulfonic acid groups makes the siloxane PC resin containing the flame-retardant segments more compatible in the system. It can exert excellent synergistic flame-retardant effect with a small amount of addition, avoids the problem of polycarbonate burning and dripping, reduces the propagation path of electric arc, and synergistically improves the CTI value. The simultaneous introduction of phenyl increases the rigidity and regularity of the molecular chain, and makes up for the adverse effect of the flame-retardant molecular chain on the mechanical properties of the system. Detailed Implementation

[0022] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.

[0023] It is worth noting that, unless otherwise specified, the compounds and related reagents used in the following preparation examples and embodiments can be purchased from the market. The PC resin used is PC 2805, purchased from Bayer Chemical Company, Germany. The intrinsic viscosity of the polybutylene terephthalate used is 1.1 dL / g. The reinforcing filler used is silane coupling agent modified glass fiber (size 10~12 μm, preparation example 6). The antioxidant used is antioxidant 1010. The ultraviolet absorber used is UV-531. The flame retardant used is phosphorus-based flame retardant TPP.

[0024] Unless otherwise specified, the post-processing steps such as "separation", "washing", "rotary evaporation", "drying", "melt extrusion", and "granulation" appearing in the following preparation examples and embodiments are routine operations for those skilled in the art, and should be selected according to actual operations.

[0025] Preparation Example 1 The preparation steps of siloxane PC resin are as follows: (1) Under a nitrogen atmosphere, 26g of 4-allyl-2-methoxyphenol and 10g of 1,1,3,3-tetramethyldisiloxane were mixed and added to 40mL of anhydrous toluene, and then 0.12g of Karstedt catalyst was added. The mixture was heated to 72℃ in a water bath and reacted for 8.5h. The intermediate was obtained by rotary evaporation. (2) Mix 0.53g of intermediate and 5g of bisphenol A in a reactor, add 30mL of 15wt% sodium hydroxide solution and 15mL of dichloromethane and stir to mix. Heat to 42℃ in a water bath, add 0.3g of triethylamine, and then add 80mL of dichloromethane solution containing 5g of triphosgene dropwise over 30min. Add 0.4g of potassium 2,5-dihydroxybenzenesulfonate, and continue to add 0.3g of triethylamine. React for 70min. After separation, washing and rotary evaporation, a solid is obtained. After washing and drying, siloxane PC resin is obtained.

[0026] Preparation Example 2 The specific preparation steps of the siloxane PC resin are the same as those in Preparation Example 1, except that 4-allyl-2-methoxyphenol in step (1) is replaced by an equal amount of 2-allylphenol.

[0027] Preparation Example 3 The specific preparation steps of the siloxane PC resin are the same as those in Preparation Example 1, except that the amount of intermediate added in step (2) is 0.75g.

[0028] Preparation Example 4 The specific preparation steps of the siloxane PC resin are the same as those in Preparation Example 1, except that the amount of potassium 2,5-dihydroxybenzenesulfonate added in step (2) is 0.6g.

[0029] Preparation Example 5 The specific preparation steps of the siloxane PC resin are the same as those in Preparation Example 1, except that potassium 2,5-dihydroxybenzenesulfonate is not added in step (2).

[0030] Preparation Example 6 The specific preparation steps of silane coupling agent modified glass fiber are as follows: glass fiber and γ-aminopropyltriethoxysilane are mixed at a mass ratio of 1:0.5 and added to an 80wt% ethanol solution (the volume ratio of γ-aminopropyltriethoxysilane to 80wt% ethanol solution is 1:50), stirred for 60 min, and dried to obtain the final product.

[0031] Example 1 A high CTI polycarbonate composite material, by weight 100%, comprises the following raw materials: 40% PC resin, 15% siloxane PC resin, 11% polybutylene terephthalate, 0.4% antioxidant, 0.7% ultraviolet absorber, 0.6% flame retardant, 3% colorant, and the balance being reinforcing filler.

[0032] The preparation method of the high CTI polycarbonate composite material in this embodiment includes the following steps: The dried PC resin, siloxane PC resin, polybutylene terephthalate, reinforcing filler, antioxidant, ultraviolet absorber, flame retardant and colorant are stirred in a high-speed mixer to obtain a mixture, which is then transferred to a twin-screw extruder and melt-extruded and granulated to obtain a high CTI polycarbonate composite material.

[0033] The drying conditions used were 105℃ for 3 hours and 1100rpm for 6 minutes. The temperatures of each section of the extruder were: Zone 1 205℃, Zone 2 215℃, Zone 3 230℃, and Zone 4 240℃. The siloxane PC resin used was obtained from Preparation Example 1.

[0034] Example 2 A high CTI polycarbonate composite material, by weight 100%, comprises the following raw materials: 35% PC resin, 10% siloxane PC resin, 10% polybutylene terephthalate, 0.2% antioxidant, 0.5% ultraviolet absorber, 0.4% flame retardant, 1% colorant, and the balance being reinforcing filler.

[0035] The preparation method of the high CTI polycarbonate composite material in this embodiment includes the following steps: The dried PC resin, siloxane PC resin, polybutylene terephthalate, reinforcing filler, antioxidant, ultraviolet absorber, flame retardant and colorant are stirred in a high-speed mixer to obtain a mixture, which is then transferred to a twin-screw extruder and melt-extruded and granulated to obtain a high CTI polycarbonate composite material.

[0036] The drying conditions used were 105℃ for 3 hours and 1200rpm for 5 minutes. The temperatures of each section of the extruder were: Zone 1 200℃, Zone 2 210℃, Zone 3 220℃, and Zone 4 230℃. The siloxane PC resin used was obtained from Preparation Example 1.

[0037] Example 3 A high CTI polycarbonate composite material, by weight 100%, comprises the following raw materials: 45% PC resin, 18% siloxane PC resin, 12% polybutylene terephthalate, 0.6% antioxidant, 1% ultraviolet absorber, 1% flame retardant, 5% colorant, and the balance being reinforcing filler.

[0038] The preparation method of the high CTI polycarbonate composite material in this embodiment includes the following steps: The dried PC resin, siloxane PC resin, polybutylene terephthalate, reinforcing filler, antioxidant, ultraviolet absorber, flame retardant and colorant are stirred in a high-speed mixer to obtain a mixture, which is then transferred to a twin-screw extruder and melt-extruded and granulated to obtain a high CTI polycarbonate composite material.

[0039] The drying conditions used were 105℃ for 3 hours and 1000rpm for 10 minutes. The temperatures of each section of the extruder were: Zone 1 210℃, Zone 2 220℃, Zone 3 230℃, and Zone 4 240℃.

[0040] The siloxane PC resin used was obtained from Preparation Example 1.

[0041] Example 4 A high CTI polycarbonate composite material and its preparation method are described. The specific implementation method is the same as that in Example 1, except that the siloxane PC resin used in this example is obtained from Preparation Example 2.

[0042] Example 5 A high CTI polycarbonate composite material and its preparation method are described. The specific implementation method is the same as that in Example 1, except that the siloxane PC resin used in this example is obtained from Preparation Example 3.

[0043] Example 6 A high CTI polycarbonate composite material and its preparation method are described. The specific implementation method is the same as that in Example 1, except that the siloxane PC resin used in this example is obtained from Preparation Example 4.

[0044] Example 7 A high CTI polycarbonate composite material and its preparation method are described. The specific implementation method is the same as that in Example 1, except that the siloxane PC resin used in this example is obtained from Preparation Example 5.

[0045] Performance testing The polycarbonate composite materials obtained in Examples 1-7 above were subjected to the following performance tests: (1) Flame retardant rating: The polycarbonate composite materials obtained in each of Examples 1-7 were tested for UL-94 flame retardant rating.

[0046] (2) Tracking index: The CTI value of the polycarbonate composite materials obtained in each of Examples 1-7 was tested according to GB / T4207-2012.

[0047] (3) Tensile strength: The tensile strength of the polycarbonate composite materials obtained in each of Examples 1-7 was tested according to the standard ASTM D 638.

[0048] The specific test results are shown in Table 1: Table 1

[0049] As shown in Table 1, the polycarbonate composite materials prepared in Examples 1-3 of this invention all have a UL-94 flame retardancy rating of V0, indicating good flame retardancy. Furthermore, their CTI values ​​are all above 635.6V, and they exhibit high tensile strength.

[0050] A comparison between Example 4 and Example 1 shows that changing the type of 4-allyl-2-methoxyphenol in step (1) can lead to changes in the tensile strength and tracking index of the polycarbonate composite material due to intermolecular forces and polar compatibility. A comparison between Example 5, Example 6 and Example 1 shows that changing the amount of intermediate and potassium 2,5-dihydroxybenzenesulfonate added in step (2) can affect the overall performance of the polycarbonate composite material. In particular, Example 6 has a significant impact on the tracking index of the polycarbonate composite material. A comparison between Example 7 and Example 1 shows that not adding potassium 2,5-dihydroxybenzenesulfonate in step (2) has little effect on the tensile strength, but the flame retardant properties and tracking index of the polycarbonate composite material fluctuate.

[0051] Finally, it should be noted that the above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it, rather than to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. This should not be used to limit the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A polycarbonate composite material with high CTI, characterized in that, The polycarbonate composite material comprises the following raw materials in terms of 100% by weight: PC resin 35-45%, siloxane PC resin 10-18%, polybutylene terephthalate 10-12%, antioxidant 0.2-0.6%, ultraviolet absorber 0.5-1%, flame retardant 0.4-1%, color powder 1-5%, and the balance of reinforcing filler.

2. The high CTI polycarbonate composite of claim 1, wherein, The PC resin is PC2805.

3. The high CTI polycarbonate composite of claim 1, wherein, The preparation steps of the siloxane PC resin are as follows: (1) under inert atmosphere, 4-allyl-2-methoxyphenol and 1,1,3,3-tetramethyldisiloxane are mixed and added into toluene, then a catalyst is added, heated to 70-80℃ by water bath, reacted for 8-9h, and then rotary evaporated to obtain an intermediate; (2) the intermediate and bisphenol A are mixed in a reactor, and then lye and dichloromethane are added and stirred, heated to 40-45℃ by water bath, a catalyst is added, then triphosgene is added dropwise, 2,5-dihydroxybenzenesulfonic acid potassium is added, and the catalyst is continuously added, reacted for 60-80min, separated, washed, and rotary evaporated to obtain a solid, which is then washed, dried, and the siloxane PC resin is obtained.

4. The high CTI polycarbonate composite of claim 3, wherein, The mass ratio of 4-allyl-2-methoxyphenol to 1,1,3,3-tetramethyldisiloxane in step (1) is (2.45-2.8):

1.

5. The high CTI polycarbonate composite of claim 3, wherein, The mass ratio of the intermediate to bisphenol A in step (2) is (0.08-0.13):

1.

6. The high CTI polycarbonate composite of claim 5, wherein, The mass ratio of 2,5-dihydroxybenzenesulfonic acid potassium to bisphenol A in step (2) is (0.05-0.1):

1.

7. The high CTI polycarbonate composite of claim 1, wherein, The reinforcing filler is one or any combination of glass fiber, calcium carbonate whisker, and silicon carbide whisker.

8. The high CTI polycarbonate composite of claim 1, wherein, The antioxidant is one or any combination of antioxidant 168, antioxidant 1010, and antioxidant 1076.

9. The high CTI polycarbonate composite of claim 1, wherein, The flame retardant is phosphorus-based flame retardant and / or nitrogen-based flame retardant.

10. A process for the preparation of a high CTI polycarbonate composite according to any one of claims 1 to 9, characterized in that, The method comprises the following steps: The dried PC resin, siloxane PC resin, polybutylene terephthalate, reinforcing filler, antioxidant, ultraviolet absorber, flame retardant, and color powder are stirred in a high-speed blender to obtain a mixture, which is transferred to a twin-screw extruder, melt-extruded, and pelletized to obtain the high-CTI polycarbonate composite material.

Citation Information

Patent Citations

  • Halogen-free flame retardant fiberglass mineral reinforced CTI polycarbonate and preparation method thereof

    CN110028772A

  • High-CTI halogen-free flame-retardant reinforced polycarbonate as well as preparation method and application thereof

    CN112341779A